A new species of Apidium (Anthropoidea, Parapithecidae) from the Sirt Basin, central Libya: First record of Oligocene primates from Libya. Issue 90 (January 2016) - Beard, K. Christopher; Coster, Pauline M.C.; Salem, Mustafa J.; Chaimanee, Yaowalak; Jaeger, Jean-Jacques
Abstract: A new species of Apidium is the most common primate currently known from a newly discovered site near Zallah Oasis in the Sirt Basin of central Libya. Based on current knowledge of the associated fauna, this new species of Apidium is early Oligocene in age, being roughly contemporaneous with faunas from Quarries G and V in the upper part of the Jebel Qatrani Formation in Egypt that also contain species of Apidium . A phylogenetic analysis based on dental characters indicates that the new species of Apidium from Libya is the sister group of Apidium phiomense . Apidium bowni and Apidium moustafai from the Jebel Qatrani Formation in the Fayum are similar in age to the new species of Apidium from Libya, but both of these Egyptian species are more distantly related to A. phiomense from younger stratigraphic levels in the Fayum. This phylogenetic pattern underscores the benefit of enhanced geographic sampling of the fossil record, even in cases where local records are thought to be reasonably comprehensive and well documented. Oligocene parapithecids can be partitioned into two clades corresponding to the subfamilies Parapithecinae (containing Parapithecus and Simonsius ) and Qatraniinae (including Qatrania and Apidium ). Climatic deterioration during the early Oligocene may have impacted the macroevolutionary dynamics of early Afro-Arabian anthropoids by fostering the fragmentation of forest habitats, thereby promoting allopatric speciation among widespread populations of Apidium and other arboreal taxa.